A MULTIMODAL ANALYSIS OF THE REPRESENTATION OF BEING SINGLE IN SELECTED 9GAG MEMES - Trisnawati, Santi (2016)
This study entitled A Multimodal Analysis of the Representation of Being Single in Selected 9GAG Memes aims to analyze, describe, and interpret how being single is represented in selected 9GAG memes and to reveal the meanings of the representations constructed in the memes. Ten memes with the topic of being single viewed from men's perspectives were taken from one of the famous comedy websites 9gag.com as the data. In conducting multimodal analysis, this study applies qualitative method. The analysis is divided into two phases. The first phase is the visual analysis, which analyzes the visual modes of the memes. The theory of visual grammar proposed by Kress and van Leeuwen (2006) is used in this phase. The next phase is the verbal analysis, which analyzes the captions of the memes. The verbal modes are analyzed using transitivity system proposed by Halliday (2004). The analyses are further discussed to reveal the meanings of the representations. The findings show that being single is represented in both positive and negative ways. However, of the ten memes analyzed, negative representations tend to dominate, associating the idea of being single to attributes such as distressing, despairing, and disappointing. In addition, the findings show that the visual and verbal modes of the memes are interrelated. They complement each other in constructing the representation of being single in the memes.; Studi yang berjudul A Multimodal Analysis of the Representation of Being Single in Selected 9GAG Memes ini bertujuan untuk menelaah, menjelaskan, dan menafsirkan bagaimana menjadi lajang direpresentasikan dalam meme di 9GAG dan untuk mengungkapkan makna dari representasi yang dibangun dalam meme tersebut. Sepuluh meme bertemakan menjadi lajang yang dilihat dari sudut pandang pria diambil dari salah satu situs komedi terkenal 9gag.com sebagai data dari studi ini. Metode kualitatif diterapkan dalam melakukan analisa multimodal pada studi ini. Analisa dalam studi ini dibagi menjadi dua fase. Fase pertama yaitu analisa visual untuk menganalisa mode visual pada meme. Teori visual grammar dari Kress dan van Leeuwen (2006) digunakan dalam fase ini. Fase selanjutnya yaitu analisa verbal untuk menganalisis tulisan yang terdapat di dalam meme. Transitivity system dari Halliday (2004) digunakan dalam menganalisis mode verbal pada meme. Temuan dari hasil analisa dibahas lebih lanjut untuk mengungkapkan makna dari representasi yang ditemukan. Temuan dari studi ini menunjukkan bahwa menjadi lajang direpresentasikan secara positif dan negatif. Namun, dari sepuluh meme yang telah dianalisa, representasi negatif cenderung mendominasi, dengan menghubungkan atribut seperti seperti menyedihkan, putus asa, dan mengecewakan. Di samping itu, temuan studi ini menunjukkan bahwa mode visual dan verbal dari meme saling berkaitan. Keduanya saling melengkapi satu sama lain dalam membangun representasi menjadi lajang pada meme.